(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the problem of developing students’ communicative competence from a pedagogical point of view. The article highlights the essence of the concept of communicative competence, its components and its role in the professional training of the student. It also clarifies the pedagogical foundations of the development of communicative competence - approaches used in the educational process, didactic principles and pedagogical conditions. It is substantiated that the development of students’ communicative competence serves to increase the effectiveness of the educational process. The article is of practical importance for professors and teachers of higher educational institutions and researchers conducting scientific research in the field of pedagogy.